Methadone poisonings: a seven‐year retrospective study of the French poison center network focusing on suicide attempts vs. misuses. (6th October 2019) - Torrents, Romain; Glaizal, Mathieu; Sinno‐Tellier, Sandra; Richard, Nathalie; Nisse, Patrick; Vodovar, Dominique; Bloch, Juliette; Simon, Nicolas; de Haro, Luc
Abstract: Methadone has been prescribed in France as opioid substitution therapy as a syrup formulation since 1995 and as capsules since 2008. Following two publications showing on a national scale the high risk of methadone poisoning in children and the lack of difference in poisoning severity between both methadone formulations, French health authorities chose to benefit from the experience acquired by the network of French poison centres concerning poisoning by this substitution medication. The aim of this study was to identify and compare the main circumstances of methadone exposure collected by a poison centre on a national scale over a period of 7 years. Retrospective descriptive study of cases of methadone exposure was compiled by the network of French poison centres between 15 October 2010 and 15 October 2017. Analysis of 1415 files revealed two major circumstances: 47% misuse and 41% suicide attempts. Severity scores evaluated according to the PSS were higher for misuse than for suicidal behaviour, despite the supposed ingested dose being statistically higher in the latter. The results also confirmed the lack of significant difference in methadone exposure between both of the formulations (syrup and capsules). This series of methadone exposure on a national scale is one of the largest compiled series in international medical literature. On the one hand, it highlights the severity of methadone poisoning (in suicidal behaviour and even more so in misuse behaviour), and on the other hand, it confirms that the capsule formulation does not seem to represent a higher risk than the syrup formulation.